2020
DOI: 10.3389/fmicb.2020.610016
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory Properties of a γ-Aminobutyric Acid-Enriched Strawberry Juice Produced by Levilactobacillus brevis CRL 2013

Abstract: Gamma-aminobutyric acid (GABA) plays a key role in mammals as the major inhibitory neurotransmitter of the central nervous system. Although GABA may not be able to cross the human blood-brain barrier, it was approved as a food ingredient because of its benefits to the host after oral administration including anti-hypertensive, anti-depressant and anti-inflammatory activities. Considering the current trend toward the development of new functional and natural products and that microbial fermentation is one of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 41 publications
0
30
0
Order By: Relevance
“…The reactions occurred with 40 µL of supernatant 108 µL of Tris/HCl buffer (160 mM (Sigma)), 6.6 µL of 2-mercaptoethanol (100 mM (Sigma)), 10 µL of α-cetoglutarato (100 mM (Sigma)), 10 µL of NADP (25 mM (Sigma)), 5.5 µL of ultrapurewater and 20 µL of GABase (Sigma). The absorbance was measured at 340 nm every 15 s for 5 min in the centering of plates with 96 cups and results were expressed as mM of the GABA [ 49 ].…”
Section: Methodsmentioning
confidence: 99%
“…The reactions occurred with 40 µL of supernatant 108 µL of Tris/HCl buffer (160 mM (Sigma)), 6.6 µL of 2-mercaptoethanol (100 mM (Sigma)), 10 µL of α-cetoglutarato (100 mM (Sigma)), 10 µL of NADP (25 mM (Sigma)), 5.5 µL of ultrapurewater and 20 µL of GABase (Sigma). The absorbance was measured at 340 nm every 15 s for 5 min in the centering of plates with 96 cups and results were expressed as mM of the GABA [ 49 ].…”
Section: Methodsmentioning
confidence: 99%
“…For example, Zhao et al investigated the antioxidant and antibacterial potential of functional strawberry juice inoculated with a starter culture of lactic acid bacteria (LAB) and yeasts [ 8 ]. A similar methodology was used by Cataldo et al in their work in which strawberry juice was inoculated with Levilactobacillus brevis to study the immunomodulatory effect of gamma-aminobutyric acid on rodent cell cultures [ 9 ]. In addition to processing into juice, studies have also shown the potential of processing strawberries into dry powders [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Gamma-aminobutyric acid (GABA) is a non-protein amino acid that can be found in plants, bacteria and animals ( 5 ). It's an important inhibitory neurotransmitter that presented in mammal central nervous system with multiple physiological functions including anti-inflammation ( 6 ). For example, GABA showed obvious anti-inflammatory effect on streptozotocin-treated mice by decreasing the synthesis of inflammatory mediators like IL-1β, TNF-α, IFN-γ, IL-12, and increasing the production of anti-inflammatory mediator TGF-β1 ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…Besides, GABA restrained the expression of inflammatory cytokines (L-6, IL8, and TNF-α) and alleviated inflammatory response of MAC-T cells induced by LPS via the TLR4-MyD88-NFκB signaling pathway ( 8 ). Except for anti-inflammation, GABA has also been reported to possess hypotensive, antidiabetic, immunity enhancement, and sedative effects, and has been applied to alleviate sleeplessness, depression and improve visual cortical function ( 6 , 9 ). Despite its various physiological functions, GABA content in natural animal- and plant-based food products is pretty low which cannot meet people's needs ( 6 ).…”
Section: Introductionmentioning
confidence: 99%